How effective is the PHC strategy highlights of the results of a survey - Bautista, Victoria A. (1989)
Three general findings are indicated by the study. These are: (1) PHC is an effective strategy in improving the health practices of the decision-makers and in improving the knowledge on health matters by the dependents in the households surveyed; (2) Level of citizen participation is a critical factor which influences health practices of the decision-makers and general awareness on health among the dependents; and (3) The Barangay Health Workers '(BHWs') performance is an important aspect in forging better health practices and in turn, the BHWs'performance is influenced by their participation for this role. Inspite of its relative effectiveness, some constraints are still discernible, the most notable of which is the lack of adequate support systems for the BHWs and the poor economic standing of the people in the communities studied.
Keywords: Medical care; Philippine Health Care (PHC); Medical care surveys